A missed diagnosis of ovarian torsion in a patient with multiple degenerating uterine fibroids: a case report - Okafor, Love C.; Ogoke, Nwakamma C.; Iseko, Kingsley I.; Meraiyebu, Aminyene Essien; Adagadzu, Simon J.; Ukoha, Chinenye (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The presentation of ovarian torsion can be dramatic with most patients presenting with acute or severe nonspecific lower abdominal and pelvic pain, either intermittent or continuous, with nausea and vomiting. The diverse clinical presentation is one major reason the diagnosis of ovarian torsion is frequently missed. The incidence of ovarian torsion ranges from 3-10% and ovarian cyst accidents constitutes about 3-5% of gynaecological emergencies. The aim was to document a case of acute abdomen suspected to be acute red degeneration of fibroids and/or acute appendicitis with incidental finding of ovarian cyst accident with consequent loss of the ovary. Our patient is a 35-year-old lady who presented with lower abdominal swelling, right sided abdominal pain and vomiting, suspected to be acute appendicitis and/or red degeneration of uterine fibroids but subsequently had exploratory laparotomy with right salpingo-oophorectomy due to right ovarian torsion, alongside myomectomy and appendectomy. Ovarian torsion is a preventable incident if early diagnosis and intervention is made. There is therefore need to consider ovarian torsion as a differential diagnosis of acute abdomen in young females to avoid loss of ovary and its function.